Preditores da participação social de idosos independentes cadastrados em estratégias de saúde da família do município de Araras/SP - Rebellato, Carolina (2016)
Social participation, besides being considered one of main goals of rehabilitation, is defined by scientific literature and some specific public policies for the elderly as one of the pillars to active aging. Nevertheless, few studies have investigated the social participation of Brazilian elderly population and its predictors. The objective of this present study was to identify the predictors of variation of the social participation of independent elderly enrolled in Family Health Strategies units in the municipality of Araras/SP. Besides investigating the dimensions of LIFE-H 3.1- Brazil and its reliability; to characterize the profile of the elderly population; to identify associations between socio-demographic, health conditions, perception of intergenerational solidarity and quality of life and to compare levels of social participation amongst elderly subgroups. A total of 175 elderly, registered in 10 Family Health Strategies of all regions of the city have participated in the present study. All data have been collected through identification form, containing social-demographic variables, from health, familiar intergenerational solidarity aspects, among parents and children, perception of quality of life, besides the following standardized instruments: Geriatric Depression Scale, Katz Scale, Mini Mental State Examination, and LIFE-H 3.1-Brasil which evaluates social participation. Data analysis has been descriptive, comparative, correlational e multivariate performed on SPSS v23.0. The evaluation of predictors of social participation was conducted by Linear Regression Analysis, taking into account the dimension of LIFE-H 3.1 previously extracted from Factor Analysis, namely: Personal Care, Community, Recreation and Communication, apart from global evaluation of social participation which involved these four dimensions (LIFE-H Total). The factorial analysis and the internal consistency of the dimensions of LIFE-H 3.1-Brazil confirm the reliability of data and utilization of such instrument in independent elderly. The association among the variables contributed to identify the factors related to health and disease condition of such population, strengthening the influence of contextual factors in this life period. Main results revealed average variations of social participation due to different variables, with special highlight on marital status, schooling, city district where he/she lives, familiar intergenerational solidarity, comorbidities, presence if depressive symptomatology, cognitive ability, physical activities practicing and subjective perception of quality of living, which were confirmed in the correlation study. The variables which acted as predictors of global social participation (LIFE-H Total) were living in specific city districts, physical activities practicing number of diseases, cognitive ability, age, depressive symptomatology, subjective evaluation of quality of life and widowhood, in that order. The variables city district, physical activity practicing, cognitive ability and subjective evaluation of quality of living acted positively, whilst other variables acted negatively in the social participation variation. This study reveals the complexity and multidimensionality of elderly social participation and the influence of personal and environmental determining factors which, mostly, could be modifiable. It is argued that maximization of actions e programs destined mainly to elderly preventive health care along with investments in infrastructure, safety and implementation of services may be of great value to the feasibility of greater social participation of such population. The continuity of these studies is desirable for deeper theoretical and empirical understanding such theme, overall the qualiquantitative and longitudinal nature to the seizure of changes, tendencies and predictors of elderly social participation in different degrees of functionality and health condition.